Switchable Fluorescent Imaging of Intracellular Telomerase Activity Using Telomerase-Responsive Mesoporous Silica Nanoparticle - Qian, Ruocan; Ding, Lin; Ju, Huangxian (Journal of the American Chemical Society, 2013)
This work designs a telomerase-responsive mesoporous silica nanoparticle (MSN) to realize in situ “off-on” imaging of intracellular telomerase activity. In the wrapping DNA (O1) sealed MSN probe, a black hole fluorescence quencher is covalently immobilized on the inner walls of the mesopores, while fluorescein is loaded in the mesopores. In the presence of telomerase and dNTPs, the designed O1 can be extended and then moves away from the MSN surface via forming a rigid hairpin-like DNA structure. Thus the O1 can act as a “biogate” to block and release fluorescein for “off-on” switchable fluorescent imaging. The MSN probe exhibits good performance for sensitive in situ tracking of telomerase activity in living cells. The practicality of this protocol has been verified by monitoring the change of cellular telomerase activity in response to telomerase-related drugs.